2018
DOI: 10.2495/eq180011
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Up the Innovation Process in the Energy Sector on the Basis of Technology Entrepreneurship

Abstract: The liberalization of the energy sector, the spreading adoption of digital information and telecommunication technologies, decentralization, and expansion of RES-based distributed generation provide broader development opportunities for technology entrepreneurship in the industry. Nevertheless, the energy sector remains one of the "least entrepreneurial" industries of the global economy-both by number of corporate innovations and by number of independent startups. Having summarized a corpus of theoretical rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…This solution is more typical for high-performance organizations and many international researchers have found that innovativeness is a very important part of high-performing enterprise configurations [51][52][53]56,57]. This model is in accordance with others authors' main findings [38,39,[54][55][56][57][58][59].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This solution is more typical for high-performance organizations and many international researchers have found that innovativeness is a very important part of high-performing enterprise configurations [51][52][53]56,57]. This model is in accordance with others authors' main findings [38,39,[54][55][56][57][58][59].…”
Section: Discussionsupporting
confidence: 89%
“…However, this is possible only in organizations with established market positions and flexible allocations of the organization's resources. We think this is an very interesting finding of the paper, because many other authors think that the high-performance organizations should be very innovative and flexible [54,56,57,130,131]. We think that is not always true.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The authors define technology entrepreneurship as team work by entrepreneurs, investors, engineers, and scientists for the sake of creating breakthrough technologies. Such joint work is fulfilled through continuous search for new opportunities and accumulation of various resources that are needed for a technological solution [30]. At the core of technology entrepreneurship is an innovation that has no rivals in the market, provides the company with long-lasting competitive advantages and creates news key competencies.…”
Section: Role Of Technology Entrepreneurship In Energymentioning
confidence: 99%
“…It is called a multi-energy system [22] for different kinds of energy have a complex coupling relationship in each cyclic process and then form an interrelated organic whole. Scholars usually regard electric power, thermal energy, and gas systems as the major research subjects of multi-energy (or integrated energy) systems [23][24][25][26][27], focusing on the internal problems of the three systems and their coordination and optimization in different manipulations at different spatial and temporal scales [28].…”
Section: Introductionmentioning
confidence: 99%